Interplays of economic and knowledge power. Neoliberal think tank networks and the return and universalization of entrepreneurship - Dieter Plehwe (Critical Perspectives on Think Tanks: Power, Politics and Knowledge, 2021)
This chapter examines the interplays of economic and epistemic power through a historical reconstruction of entrepreneurship ideas in management and economics and a historical social network analysis linking intellectuals and think tanks to foundations and corporations. With a focus on ideas, concepts and storylines, this study helps shed light on the intellectual and ideological origins of modes of thinking - and the ways of life based on them - that have become invisible or taken for granted. Although the continuing relevance and even the existence of neoliberalism are doubted by many, entrepreneurship discourses have become increasingly influential in contemporary society. This chapter illustrates how the original conception, or rather revision, of entrepreneurship ideas and their promotion by neoliberal intellectuals and think tanks preceded the diffusion of entrepreneurship ideas via business schools and consulting companies. This was followed by the subsequent universalization of entrepreneurship discourses and related arrangements in media and society, respectively: from social security regimes (activation, self-responsibility, and so on) to entrepreneurial universities on to charity and philanthropy (social entrepreneurship, eco-entrepreneurship).
Keywords: 300